DESAIN DAN VALIDASI PERANGKAT PERCOBAAN KALORIMETER GAS SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Fenny Suhartiwi; Zulirfan '; Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purposed of this reserach and development study is to produce an experiment’s device of gas calorimeter as a physics learning media of senior high school students. This device consist of the tool kit and user manual. There were 5 expert in physics learning have been participated in the validity process of this research. The research found that the gas calorimeter tool kit and user manual has a good criteria as physics learning media.Keywords: Design and Validation, Research and Development, Gas Calorimeter tool kit.